2003
DOI: 10.1021/op020225p
|View full text |Cite
|
Sign up to set email alerts
|

Process Improvements for the Preparation of Kilo Quantities of a Series of Isoindoline Compounds

Abstract: A series of isoindoline analogues with either an indazole (HMR 2934, HMR 2651) or benzisoxazole (HMR 2543) appendage were prepared for the proposed treatment of psychiatric disorders such as obsessive compulsive disorder and attention deficit disorder. The isoindoline compounds were prepared by reduction of the corresponding phthalimides with LiAlH 4 . One compound was not chiral, and the other two required an enantioselective synthesis. The key step for these optically active analogues involved the coupling b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Some fluorinated chalcone derivatives are reported to possess anti-inflammatory activity due to their influence on nitric oxide production 10 . Fluorinated 3-aminoindazoles have been identified as lead compounds for the treatment of psychiatric disorders such as obsessive compulsive disorder and attention deficit disorder 11 . In addition, they are reported to be useful in the treatment of diseases associated with protein kinase, e.g., diabetes, cancer and Alzheimer's diseases 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Some fluorinated chalcone derivatives are reported to possess anti-inflammatory activity due to their influence on nitric oxide production 10 . Fluorinated 3-aminoindazoles have been identified as lead compounds for the treatment of psychiatric disorders such as obsessive compulsive disorder and attention deficit disorder 11 . In addition, they are reported to be useful in the treatment of diseases associated with protein kinase, e.g., diabetes, cancer and Alzheimer's diseases 12 .…”
Section: Introductionmentioning
confidence: 99%
“…N -alkyl amines can be obtained by the catalytic amination of alcohols [ 30 ] or by the reaction of the respective amine with alkyl halides and an auxiliary base [ 31 ]. Heterocyclic N -imides have also been smoothly converted into the corresponding amines with LiAlH 4 in excellent yields [ 32 , 33 ]. This route was initially adopted for the synthesis of amines 11a – d from the previous synthesized imides ( Scheme 2 , method D).…”
Section: Resultsmentioning
confidence: 99%
“…Watson et al [ 32 ] showed that the reduction of the phthalimide functionality might be problematic due to the comparatively facile oxidation of the emerging isoindoline to the respective isoindole. Surprisingly, the conversion of phthalimide 7a with LiAlH 4 gave essentially the isoindoline, 11a, in good yields, whereas the reduction to the amines, 11b – d , failed.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, by taking note of the work of Watson et al 29 and of Vetuschi et al 30 we have developed a third strategy of synthesis starting from O-benzyl-D-serine (Scheme 8). The synthesis begins with a diazotation reaction in presence of sodium nitrite to give hydroxyacid (R)-20 with retention of configuration {½a 22 D ¼ À2 (c 0.5, EtOH)} which could be explained by the carbonyl assistance of the carboxylic group as shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%